Pengolahan Data Keuangan Dengan Menggunakan Zahir Accounting 5.1 Pada PT. Sigma Pikir Teladan - Utami, Lila Dini; Hidayat, Rahmat (www.bsi.ac.id, 2018)
In this era of globalization, technology is growing very fast, especially in the field of software technology and hardware, where the development of many provide many benefits for us. The various areas of the company are greatly assisted in the advancement of this technology. The weakness of financial data processing process manually will be vulnerable to mistakes in the process of financial records, resulting in less accurate reports made. PT Sigma Pikir Teladan is a company engaged in forestry consulting services. Existing systems in PT Sigma Pikir Teladan still done manually, ranging from recording corporate expenses to income receivedby the company. On this occasion the author tries to make the final task by implementing the process of recording financial data at PT Sigma Pikir Teladan using Zahir Accounting Software Version 5.1, which during this process has not been computerized. It is expected that with the application of this application process of financial recording at PT Sigma Pikir Teladan become more effective and efficient in supporting activity of financial data processing at this company.